2001
DOI: 10.4049/jimmunol.166.2.868
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Dependent B and T Lymphocyte Activation Is Mediated by the Secretion of Immunologically Active Exosomes

Abstract: Mitogenic activity of bone marrow-derived mouse mast cells and mast cell lines P815 and MC/9 on B and T lymphocytes is present in their culture supernatants. To identify this activity, mast cells were incubated in serum-free medium and the supernatant was subjected to differential centrifugation, which resulted in two fractions, the hypodense and dense fraction (pellet). When analyzed for their mitogenic activity on spleen cells, all activity was found to be associated with the dense fraction. Electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
221
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(234 citation statements)
references
References 33 publications
2
221
2
5
Order By: Relevance
“…Mast cells express MHC class I and II molecules, and have been reported to process and present antigen in vitro (reviewed in REFS 13,[43][44][45] ). Mast cells also can enhance antigen presentation in vitro by internalizing antigen bound to high-affinity Fc receptor for IgE (FcεRI)-associated IgE; this mechanism is independent of mast-cell MHC class II expression, but requires mastcell apoptosis and phagocytosis by other antigen-presenting cells, which then present the antigen 45 .…”
Section: Mast-cell Immunomodulatory Functions Immunomodulatory Activimentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cells express MHC class I and II molecules, and have been reported to process and present antigen in vitro (reviewed in REFS 13,[43][44][45] ). Mast cells also can enhance antigen presentation in vitro by internalizing antigen bound to high-affinity Fc receptor for IgE (FcεRI)-associated IgE; this mechanism is independent of mast-cell MHC class II expression, but requires mastcell apoptosis and phagocytosis by other antigen-presenting cells, which then present the antigen 45 .…”
Section: Mast-cell Immunomodulatory Functions Immunomodulatory Activimentioning
confidence: 99%
“…Mast cells represent potential sources of many mediators that can enhance or suppress the development, survival, proliferation, migration, maturation, or function of immune cells (reviewed in REFS [1][2][3][5][6][7][8]13,[16][17][18]21,30,31,43,44,[46][47][48][49][50][51][52][53][54][55][56]. Some individual mediators, such as histamine, can have both positive and negative immunomodulatory effects.…”
Section: Mast-cell Immunomodulatory Functions Immunomodulatory Activimentioning
confidence: 99%
“…Mast cell exosomes also participate in the immune response since they have the capacity to stimulate B and T cell proliferation and cytokines production such as IL-2 and IFN [91]. It was shown that peptide-loaded exosomes from mast cells elicit an efficient antibodies production in-vivo following a subcutaneous injection in mice.…”
Section: Stimulation Of Immunocompetent Cellsmentioning
confidence: 99%
“…Opposite to the potent immune stimulatory properties of exosomes issued from immunocompetent cells, many studies have demonstrated that tumor cell-derived exosomes display detrimental effects on immune response against tumors, leading to suppressive pathways hampering immune defenses in patients [91]. Consequently, tumor exosomes may contribute to tumor growth and to participate in tumor evasion.…”
Section: Tumor Promoter Activitymentioning
confidence: 99%
“…Exosomes are small MHC-II-bearing vesicles (50 -90 nm) that originate from late endosomes and are secreted by a broad array of hemopoietic and epithelial cells (62)(63)(64)(65). The molecular characterization of dendritic cell-derived exosomes highlighted the presence, among others, of HSP hsc73 and CD86.…”
Section: Discussionmentioning
confidence: 99%